2020
DOI: 10.1038/s41541-020-00238-8
|View full text |Cite
|
Sign up to set email alerts
|

Technological approaches to streamline vaccination schedules, progressing towards single-dose vaccines

Abstract: Vaccines represent the most successful medical intervention in history, with billions of lives saved. Although multiple doses of the same vaccine are typically required to reach an adequate level of protection, it would be advantageous to develop vaccines that induce protective immunity with fewer doses, ideally just one. Single-dose vaccines would be ideal to maximize vaccination coverage, help stakeholders to greatly reduce the costs associated with vaccination, and improve patient convenience. Here we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 216 publications
(293 reference statements)
0
19
0
Order By: Relevance
“…Sinovac found that, for their whole-inactivated virus (WIV) vaccine, extending the COVID-19 vaccine dosing interval from 2 to 4 weeks might have improved neutralizing antibody titers 12 . Although closer spacing of doses might be advantageous during an outbreak, optimizing the schedule for magnitude and durability of induced responses might potentially make future COVID-19 vaccine campaigns more practical because they allow national programs time to plan and execute more effectively 29,30 .…”
Section: Scientific Questionsmentioning
confidence: 99%
“…Sinovac found that, for their whole-inactivated virus (WIV) vaccine, extending the COVID-19 vaccine dosing interval from 2 to 4 weeks might have improved neutralizing antibody titers 12 . Although closer spacing of doses might be advantageous during an outbreak, optimizing the schedule for magnitude and durability of induced responses might potentially make future COVID-19 vaccine campaigns more practical because they allow national programs time to plan and execute more effectively 29,30 .…”
Section: Scientific Questionsmentioning
confidence: 99%
“…Subunit vaccines include a component of the target pathogen which evoke an immune reaction that is unique to that section ( 122 ). While baculovirus-expressed Rinderpest virus (RPV) “H” and “F” proteins were used as antigens for subunit vaccines, they did not provide protection in cattle against virulent RPV despite eliciting a robust neutralizing antibody response ( 123 ).…”
Section: Subunit Vaccines and Virus-like Particles (Vlps)mentioning
confidence: 99%
“…The development of encapsulation techniques for target orientated drug delivery to organs and delayed relief of drug agents have also influenced the field of cell and gene therapy during the last two decades [ 34 , 35 ]. However, cell products for the treatment of PAD or critical limb ischemia have demonstrated only modest results or failed in clinical studies due to poor cell retention within the ischemic microenvironment [ 36 , 37 , 38 ].…”
Section: Encapsulation Techniques For Cell Transplantsmentioning
confidence: 99%